Christianity 1 - Penney, Sue. (Austin, Tex. : Raintree Steck-Vaughn, 1997)
Discusses the origins, history, evolution, and celebrations of Christianity.
Includes( index.)
Keywords: Christianity -- Juvenile literature; Christianity